Perancangan Aplikasi Sistem Monitoring Kondisi Lalu Lintas Berbasis Android - Hadi Anwarsyah; Muhammad Farid Firdaus; Aninda Agustin Nurfajrina; Sofyan Mufti Prasetiyo (CV. Multi Kreasi Media, 2023)
Traffic congestion is undoubtedly one of the most common problems in big cities, and one of them is the city of Bandung. The inherent effects of congestion include delays for road users, wasted energy, possibly increased air pollution, increased stress on road users, disrupted the smooth operation of emergency vehicles such as ambulances and fire engines. There are several factors that cause traffic jams, such as traffic jams and bad weather. Sometimes the weather cooperates Every place is different even though they are still in the same city. This is an unpredictable situation for road users, so road users are not prepared for this condition.